Cyclin-dependent kinase inhibitor 1 plays a more prominent role than activating transcription factor 4 or the p53 tumour suppressor in thapsigargin-induced G1 arrest - Erin van Zyl; Claire Peneycad; Evan Perehiniak; Bruce C. McKay (PeerJ, 2023)
Background Thapsigargin (Tg) is a compound that inhibits the SERCA calcium transporter leading to decreased endoplasmic reticulum (ER) Ca2+ levels. Many ER chaperones are required for proper folding of membrane-associated and secreted proteins, and they are Ca2+ dependent. Therefore, Tg leads to the accumulation of misfolded proteins in the ER, activating the unfolded protein response (UPR) to help restore homeostasis. Tg reportedly induces cell cycle arrest and apoptosis in many cell types but how these changes are linked to the UPR remains unclear. The activating transcription factor 4 (ATF4) plays a key role in regulating ER stress-induced gene expression so we sought to determine if ATF4 is required for Tg-induced cell cycle arrest and apoptosis using ATF4-deficient cells. Methods Two-parameter flow cytometric analysis of DNA replication and DNA content was used to assess the effects of Tg on cell cycle distribution in isogenic HCT116-derived cell lines either expressing or lacking ATF4. For comparison, we similarly assessed the Tg response in isogenic cell lines deleted of the p53 tumour suppressor and the p53-regulated p21WAF1 cyclin-dependent kinase inhibitor important in G1 and G2 arrests induced by DNA damage. Results Tg led to a large depletion of the S phase population with a prominent increase in the proportion of HCT116 cells in the G1 phase of the cell cycle. Importantly, this effect was largely independent of ATF4. We found that loss of p21WAF1 but not p53 permitted Tg treated cells to enter S phase and synthesize DNA. Therefore, p21WAF1plays an important role in these Tg-induced cell cycle alterations while ATF4 and p53 do not. Remarkably, the ATF4-, p53-and p21WAF1-deficient cell lines were all more sensitive to Tg-induced apoptosis. Taken together, p21WAF1 plays a larger role in regulating Tg-induced G1 and G2 arrests than ATF4 or p53 but these proteins similarly contribute to protection from Tg-induced apoptosis. This work highlights the complex network of stress responses that are activated in response to ER stress.